Transportin-1: A Nuclear Import Receptor with Moonlighting Functions - Mboukou, Allegra; Rajendra, Vinod; Kleinova, Renata; Tisné, Carine; Jantsch, Michael F.; Barraud, Pierre (Frontiers in Molecular Biosciences, 2021)
Transportin-1 (Trn1), also known as karyopherin-β2 (Kapβ2), is probably the best-characterized nuclear import receptor of the karyopherin-β family after Importin-β, but certain aspects of its functions in cells are still puzzling or are just recently emerging. Since the initial identification of Trn1 as the nuclear import receptor of hnRNP A1 ~25 years ago, several molecular and structural studies have unveiled and refined our understanding of Trn1-mediated nuclear import. In particular, the understanding at a molecular level of the NLS recognition by Trn1 made a decisive step forward with the identification of a new class of NLSs called PY-NLSs, which constitute the best-characterized substrates of Trn1. Besides PY-NLSs, many Trn1 cargoes harbour NLSs that do not resemble the archetypical PY-NLS, which complicates the global understanding of cargo recognition by Trn1. Although PY-NLS recognition is well established and supported by several structures, the recognition of non-PY-NLSs by Trn1 is far less understood, but recent reports have started to shed light on the recognition of this type of NLSs. Aside from its principal and long-established activity as a nuclear import receptor, Trn1 was shown more recently to moonlight outside nuclear import. Trn1 has for instance been caught in participating in virus uncoating, ciliary transport and in modulating the phase separation properties of aggregation-prone proteins. Here, we focus on the structural and functional aspects of Trn1-mediated nuclear import, as well as on the moonlighting activities of Trn1.